Recent Progress in the Chemical Upcycling of Plastic Wastes - Chen, Xi; Wang, Yudi; Zhang, Lei (ChemSusChem, 2021)
The massive generation of plastic wastes without satisfactory treatment has induced severe environmental problems and gained increasing attentions. In this Minireview, recent progresses in the chemical upcycling of plastic wastes by using various methods (mainly in the past three to five years) is summarized. The chemical upcycling of plastic wastes points out a “plastic‐based refinery” concept, which is to use the plastic wastes as platform feedstocks to produce highly valuable monomeric or oligomeric compounds, putting the plastic wastes back into a circular economy. The different chemical methods to upcycle plastic wastes, including hydrogenolysis, photocatalysis, pyrolysis, solvolysis, and others, are introduced in each section to valorize diverse plastic feedstocks into value‐added chemicals, materials, or fuels. In addition, other emerging technologies as well as the new generation of plastic thermosets are covered. What a waste: The chemical upcycling of plastic wastes offers a powerful and efficient strategy to utilize the waste as a resource for a diversity of valuable fuels, chemicals, and materials. The recent advances in this field are introduced in the Minireview.